PARAMETER GENETIK PADA UJI KLON JATI (Tectona grandis L. F) UMUR 5,5 TAHUN DI SUMATERA SELATAN - Imam Muslimin; Agus Sofyan; Syaiful Islam (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
The objectives of study were to ascertain the level of genetic variation, and to estimate heritability and expected genetic gains in tree height, diameter and volume of teak clonal test. Thirty five clones were tested at KHDTK Kemampo, South Sumatra. At 5.5 years of age there were genetic variations among clones in tree height and diameter, but the variation was relatively low. The mean height and diameter were 11.53+2.15 m and 12.85+2.73 cm respectively. The contribution of the genetic component to total variation was relatively low, namely 5.39 %, 4.20 % and 6,96% for height, diameter and volume respectively. Individual broad sense heritabilities were 0.06, 0.05 and 0.07 for height, diameter and volume respectively, while broad sense heritabilities on clone mean level were 0.33, 0.26, and 0.29 respectively for tree height, diameter and volume. By selecting the best ten clones, the expected genetic gains for height, diameter and volume were 3.12%, 2.80 % and 10.65%, respectively. Genetic correlation between height and diameter was 1.01.